Benign prostatic hyperplasia prevention: from a nursing perspective (Research, Society and Development, 2022)
Objective: To discuss the challenges of benign prostatic hyperplasia prevention in primary care. Materials and Methods: This is an integrated literature review study. For data collection virtual research libraries were used: online scientific electronic library (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS), "National Library of Medicine" (PubMed). Results: Studies highlighting the difficulties and challenges faced by nurses in the prevention of Benign Prostatic Hyperplasia in Primary Health Care are the lack of government resources, financial resources, and management of health care units. Conclusion: It is necessary that nursing professionals act actively in the communities where they provide assistance, to perform the nursing consultation and emphasize that primary health care has the following functions: prevention, promotion, early detection and palliative care to patients diagnosed with Benign Prostatic Hyperplasia. In addition, it is the patient's right to receive health care services through the Unified Health System (UHS).